A First Step for Technology Integration for Teachers - Rena Cifarelli (Networks: An Online Journal for Teacher Research, 1999)
How do I begin to work with teachers on integrating technology into their diverse disciplines? How do I begin to form a relationship that allows them to express their fears about technology and trust in me to overcome those fears? How do I assess their technology strengths and weaknesses so I can help them to begin at a point where they are comfortable with the technology? These were the initial questions I asked myself as a high school educational technologist, who was beginning to embark with a group of four other teachers on an action research project.